Antibacterial activity of plant phytochemicals on antibiotic-resistant bacteria isolated from meat - Morsy, Zeinab M.; Ghaly, Mohamed F.; Elariny, Eman Y. (Journal of Advanced Veterinary Research, 2024)
Multidrug resistance poses a danger to public health and steadily raises mortality, despite the discovery and development of a wide range of antimicrobial drugs. Developing practical solutions to address these problems has been the focus of many recent studies. In this work, we elucidate the way certain antibiotics, when coupled with other antimicrobial agents like plant extracts, can produce synergistic effects provided that each therapy targets a separate target or signaling pathway and functions via a different mechanism. Gas chromatography-mass spectrometry (GC-MS) and thin-layer chromatography (TLC) were used to identify bioactive metabolite extracts and purify plant extracts with active antibacterial qualities. The minimum inhibitory concentration (MIC) was determined using the broth microdilution method. Different 100 samples of meat (fresh, frozen Brazilian, Sudanese, and minced meat) and meat products such as pastrami, burgers, kofta, luncheon, and sausage were randomly collected from six (6) different locations in Al-Sharkia Governorate, Egypt. The associated pathogenic bacteria recovered from the isolated raw meat samples identified by microbiological, biochemical, and molecular methods is Bacillus. Clove extract was found to be the most effective and exhibited bacteriostatic and bactericidal activities against highly resistant strains of pathogenic bacteria. The plant extracts used in the study have great efficacy in reducing bacterial contamination and can be used as a safe alternative to antibiotics to avoid and control foodborne diseases.